Literature Review of Deep Learning Integrated E-Learning Media Research Trend in Mathematics 2022-2026 - Asila Maharani Arif; Trimurtini Trimurtini (FKIP - Universitas Riau, 2026)
The main issue in this study is how effective the use of e-learning media in improving the quality of mathematics learning. The purpose of this study was to review research trends related to the integration of deep learning into e-learning media in the field of mathematics. The research method used was a Systematic Literature Review (SLR) involving 2,540 articles. After the exclusion process, 25 articles published between 2022-2026. The exclusion criteria for article selection were based on empirical research relevant to the topic of deep learning in mathematics through electronic media, published in accredited journals, written in Indonesian or English, and available in full text. The research findings indicate that (1) the trend in research on e-learning media integrated with deep learning shows a fluctuating pattern during the 2022–2026 period, (2) most studies were conducted at Universitas Negeri Surabaya and Universitas PGRI Adi Buana Surabaya, (3) the learning approaches used were PBL and ARCS, (4) numbers were the most dominant topic, and (5) websites were the most commonly used type of e-learning medium. The results of this study can serve as a reference for developing deep learning-based e-learning materials to improve the effectiveness of mathematics instruction.